Perfect machine - Savory, Brett Alexander, 1973- (Angry Robot, 2017)
Henry Kyllo is a Runner, a member of a secret society called the Inferne Cutis. Every day he is chased through the city by Hunters whose goal is to fill him with bullets. It is a secret war steeped in history, tradition, and mutual fear. Rumors abound about what happens when a Runner achieves ascension, but it has supposedly never happened before, so no one knows for sure. Except that it has happened before. And it is happening again.